Family law in America - Katz, Sanford N., 1933- (New York, NY : Oxford University Press, 2021)
This volume examines the state of family law in America. Among its themes is the tension between individual autonomy and governmental regulation in all aspects of family law. It examines both conventional and new definitions of formal and informal domestic relationships.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 20, 2021).
Keywords: Domestic relations -- United States